Response of African oil bean (Pentaclethra Macrophylla Benth) seeds to soils contaminated with spent lubricating oil - O. M. Agbogidi (Global Journal of Food and Agribusiness Management, 2019)
This study evaluated the response (seedling emergence) of Pentaclethra macrophylla seeds sown in soils contaminated with spent lubricating oil using 0, 1, 2, 4 and 8% w/w in Asaba, Delta State in 2009. The results showed that 100% of the seeds sown in the control germinated. Significant reductions (P  0.05) were however recorded in seeds planted in the soils treated with the spent lubricating oil. The effects being concentration dependent. The study has shown that spent lubricating oil has a highly significant (P  0.05) effect of reducing the germination percentage and rate of germination of P. macrophylla as well as increasing the days to germination of this multipurpose tree species.